Late Coarctation Presenters Suffer Chronic Hypertension Resisting to Medicine Treatment - Andreas C Petropoulos; Maria Moschovi; Aynur Xudiyeva; Fexreddin Qarayev; Ibrahim Isayev (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2017)
Coarctation of the aorta (CoA) is a common Congenital Heart Disease (CHD) presenting with many symptoms and signs, in any age group. From its dramatic appearance as a part of Hypo plastic Left Heart Syndrome(HLHS), to early Congestive Heart Failure(CHF)in neonatal and early infantile age, to undetected Hypertension (HTN) in early or even late adulthood. The aim of this short review is to present this unique CHD, underline the presentation of late detected CoA, presenting with HTN and its impact in treating resistant HTN even after successful surgical treatment. Finally, the late onset HTN, following successful surgical treatment and its medicine management will be addressed. This difficult to control on mono or dual pharmacotherapy and the late complications of persistent uncontrolled HTN is the basic reason that these patients are a long-life follow-up population with important medical needs and increasing morbidity and mortality.